Pengembangan Teknologi 3d Augmented Reality Sebagai Media Visual Sistem Peredaran Darah Berbasis Wahdatul Ulum - Nahombang, Syntia; Rasyidah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
The purpose of this study was to design a 3D augmented reality (AR) learning medium using the assemblr edu platform, integrated with Qur”anic verses through the wahdatul ulum approach, focusing on the circulatory system material for grade XI senior high school students (SMA/MA). This research applied the Research and Development (R&D) method by referring to the ADDIE model. The instruments employed consisted of interview sheets, validation sheets, questionnaires, and learning outcome tests. The findings revealed that (1) the validation score from media experts reached 92,5%; (2) material experts scored 95,4%; (3) test instrument validators obtained 87,5%; (4) validators of wahdatul ulum integration achieved 92,5%; all of which were categorized as very valid. The practicality test indicated that (1) teacher responses reached 91% and (2) student responses reached 93,5%, both of which fell into the very practical category. The effectiveness of the media, based on the comparison between pretest and posttest result, showed an increase in the average score from 82,2 to 95,4, with an N-Gain value of 0,74 categorized as high. The results demonstrate that the 3D augmented reality visual media based om wahdatul ulum is valid, practical, and effective for biology learning, as it successfully enhances student’s understanding, interest, and active participation in visualizing complex concepts interactively while simultaneously instilling spiritual values through the integration of qur’anic verses.